Traumatic Brain Injury - Moreira Monteiro, Jander; Manzi, Joao; Marttos, Antonio; Collaço, Iwan Augusto; Santos Filho, Carlos Alberto dos [UNESP]; Zanini, Marco Antonio [UNESP]; Hamamoto Filho, Pedro Tadao [UNESP]; Graciolli Cordeiro, Joacir (Springer Nature, 2025)
Traumatic brain injury (TBI) is one of the most important causes of death, especially among young people, such as victims of car accidents and physical aggression. Also, it is often associated with a high morbidity rate among people in the economically active population age range, with sequelae that can be permanent, leading to a high social and economic cost. Therefore, it has become a topic of great relevance and impact on health policies and socioeconomic programs around the world.